Study of pathological lesions in rats after the experimental administration of Lindane - PAPAIOANNOU (Ν. ΠΑΠΑΪΩΑΝΝΟΥ), N.; KELLER-SAMOUILIDOU (ΓΚ. ΚΕΛΛΕΡ-ΣΑΜΟΥΗΛΙΔΟΥ), G.; LEKKAS (Σ. ΛΕΚΚΑΣ), S.; KOTSAKI-KOVATSI (Β. Π. ΚΩΤΣΑΚΗ-ΚΟΒΑΤΣΗ), V. P.; KOVATSI (Α. ΚΟΒΑΤΣΗΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this experimental study, the lesions that are caused from the chemical substance Lindane were studied. Sixteen rats were used as experimental animals. The substance was orally administered, with food, to 10 rats (5 females and 5 males) in a dose of 8,2 mg/kg b.w./3 days during the first 10 days and in a dose of the 33 mg/kg b.w./ 2 days during the following 40 days. The remaining 6 rats (4 females and 2 males) were used as controls. The mainly clinical symptoms which were observed in the experimental animals, in the end of the experimentation, were anorexia, lethargy, hypothermia and muscular rigor. All the rats were sacrificed 5 days after the administration of the last dose of the substance and they were autopsied. In the macroscopical examination oedema and vascular hyperhaemia were observed in the brain. In the histological examination spongiosis of the white matter of the brain, interstitial pneumonia, oedema and loss of the cross striation of the cardiac muscle cells, coagulative necrosis of individual groups of hepatic cells and degeneration of the epithelial cells of the urinary tubules were detected. In conclusion, when Lindane is administered in subtoxical doses for a long period of time it is possible to cause damages to the organism of the experimental animals, which are located mainly in the brain and secondary in the liver, the kidneys and the other organs.